2021
DOI: 10.3390/ani11092754
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Antimicrobial Susceptibility and Virulence Gene Characterization Associated with Staphylococcus aureus Carriage in Healthy Camels from Tunisia

Abstract: A total of 318 nasal and rectal swabs were collected from 159 apparently healthy camels (Camelus dromedarius) randomly selected from five regions in southern and central Tunisia and screened for Staphylococcus aureus carriage. Staphylococcus spp. were recovered from 152 of 159 camels studied (95.6%) and in total 258 swabs (81%) were positive. Among these isolates, 16 were coagulase positive Staphylococcus (CoPS) (6.2%) and were characterized by biochemical and molecular tests as S. aureus. These were isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 57 publications
(82 reference statements)
4
11
0
Order By: Relevance
“…The CPS group is commonly associated with severe infections [ 16 ]. Earlier studies conducted on healthy camels in several African and Middle Eastern nations have reported a variable prevalence of S. aureus in nasal carriage, ranging from 6.2% to 89.1% [ 40 , 41 ]. The reasons for this variability are unknown, though it may be due to differences in shared environments or urban lifestyles associated with breeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CPS group is commonly associated with severe infections [ 16 ]. Earlier studies conducted on healthy camels in several African and Middle Eastern nations have reported a variable prevalence of S. aureus in nasal carriage, ranging from 6.2% to 89.1% [ 40 , 41 ]. The reasons for this variability are unknown, though it may be due to differences in shared environments or urban lifestyles associated with breeding.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, the camels were in traditional farming communities, and the antibiotics may not be widely available or affordable, leading to limited or no use of antibiotics in treating bacterial infections, and thus a low selective pressure is assumed. However, there are few studies available on the general level of antimicrobial use in dromedaries or antimicrobial resistance in bacteria from dromedaries, and the interpretation remains difficult [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ST88-t786 and other ST88 clones of t186, t1603, and t729 have frequently been detected in humans, food. or food animals ( 33 , 37 39 ). This further suggests potential transmission among the above-mentioned hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Acquisition of methicillin resistance is due to integration of the staphylococcal cassette chromosome mec (SCC mec ), which contains the mecA gene conferring resistance to β-lactams [ 13 ]. In 2011, A divergent mecA homologue, mecA LGA251 , later named mecC , was discovered and located in a novel staphylococcal cassette chromosome mec element, designated SCC mec type-XI [ 14 ]. The mecC was 70% identical to the mec A gene and was initially detected in 15 S. aureus isolates from dairy cattle in England [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, A divergent mecA homologue, mecA LGA251 , later named mecC , was discovered and located in a novel staphylococcal cassette chromosome mec element, designated SCC mec type-XI [ 14 ]. The mecC was 70% identical to the mec A gene and was initially detected in 15 S. aureus isolates from dairy cattle in England [ 14 ].…”
Section: Introductionmentioning
confidence: 99%